Significant variations in Weber fraction for changes in inter-onset interval of a click train over the range of intervals between 5 and 300 ms - Ungan, Pekcan; Yagcioglu, Suha (Frontiers in Psychology, 2014)
It is a common psychophysical experience that a train of clicks faster than ca. 30 per second is heard as one steady sound, whereas temporal patterns occurring on a slower time scale are perceptually resolved as individual auditory events. This phenomenon suggests the existence of two different neural mechanisms for processing of auditory sequences with fast and slow repetition rates. To test this hypothesis we used Weber’s law, which is known to be valid for perception of time intervals. Discrimination thresholds and Weber fractions (WF) for twelve base inter-click intervals (ICI) between 5 ms and 300 ms were measured from ten normal hearing subjects by using an “up-down staircase” algorithm. The mean WF, which is supposed to be constant for any perceptual mechanism according to Weber’s law, displayed significant variation with click rate. WFs decreased sharply from an average value of around 5% at repetition rates below 20 Hz to about 0.5% at rates above 67 Hz. Parallel to this steep transition, subjects reported that at rates below 20 Hz they perceived periodicity as a fast tapping rhythm, whereas at rates above 50 Hz the perceived quality was a pitch. Such a dramatic change in WF indicated the existence of two separate mechanisms for processing the click rate for long and short ICIs, based on temporal and spectral features, respectively. A range of rates between 20 Hz and 33 Hz, in which the rate discrimination threshold was maximum, appears to be a region where both of the presumed time and pitch mechanisms are relatively insensitive to rate alterations. Based on this finding, we speculate that the interval-based perception mechanism ceases to function at around 20 Hz and the spectrum-based mechanism takes over at around 33 Hz; leaving a transitional gap in between, where neither of the two mechanisms is as sensitive. Another notable finding was a significant drop in WF for ICI=100 ms, suggesting a connection of time perception to the EEG alpha rhythm.